Use of the 6-minute walk/run test to predict peak oxygen uptake in adolescents - Gabriel Bergmann; Mauren Bergmann; Antônio de Castro; Thiago Lorenzi; Eraldo Pinheiro; Rodrigo Moreira; Alexandre Marques; Adroaldo Gaya (Revista Brasileira de Atividade Física e Saúde)
This study aimed to create an equation to predict peak oxygen uptake from data of the 6-minute walk/run test and demographic and anthropometric variables in adolescents. The results of the 6-minute walk/run (6WRT), peak oxygen uptake, height, body weight and body mass index (BMI) in 125 adolescents age 10 to 14, of which 66 were female, were assessed. They were divided into a validation and a cross-validation group. A linear regression analysis was conducted to assess the associations between the independent variables 6WRT, age, gender, anthropometric measurements and the dependent variable peak oxygen uptake in the validation group. The Bland-Altman method was used to test agreement between measured and estimated values. It was found that the best model to predict peak oxygen uptake included the 6-minute walk/run test, BMI, and gender. These variables presented a multiple correlation coefficient of 0.77 and a standard error of estimate of 3.99 [(mL/kg)/min]. The accuracy of the model was tested by applying the equation created in the validation group to the cross-validation group and total sample. The Bland-Altman method results did not indicate any systematic bias or heteroscedasticity in both the validation and cross-validation groups. In conclusion, our multiple regression equation [peak oxygen uptake = 41.946 + 0.022(6WRT) – 0.875(BMI) + 2.107(gender)] is adequate for predicting peak oxygen uptake in adolescents age 10 to 14.